Fabrication of nitrogen doped and hierarchically porous carbon flowers for CO2 adsorption. Issue 51 (September 2021) - Shi, Jinsong; Cui, Hongmin; Xu, Jianguo; Yan, Nanfu; Zhang, Chao; You, Shengyong
Graphical abstract: Highlights: Nitrogen doped carbon flower is prepared using glucose as the carbon source. The formation mechanism of the flower shape is proposed and discussed. The carbon flower has high nitrogen content of 9.31–11.91 wt %. The carbon flower exhibits hierarchically marco-meso-microporous structure. Nitrogen doping shows strong influence on CO2 /N2 selectivity. Abstract: Porous carbon with specifically designed structure as CO2 adsorbent is a very attractive and interesting research topic. In this study, we presented the synthesis and CO2 adsorption of flower shaped porous carbons. Flower-like hydrochar derived from the hydrothermal reaction of glucose, cobalt sulfate, and hexamethylenetetramine was used as the precursor, which was converted to carbon flower during CO2 activation. The flowers had hierarchically macro-meso-microporous structure. Interspaces and voids were formed by assembly of the petals, and the petals were distributed with pores of different scales. The formation mechanism of, and influences of various synthesis parameters on the flower shape were studied and analyzed. The carbon flowers exhibited surface area of 422−691 m 2 /g, and very high nitrogen content of 9.31–11.91 wt%. CO2 adsorption performances of the carbon flowers were also studied. Influences of the textural properties and doped nitrogen on the adsorption performances were investigated. The experiment results demonstrated that nitrogen doping showed positive effects on CO2 uptake at 1 bar, and had strong influence on the CO2 /N2 selectivity.